(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The research aims, in general, to know the extent of the importance of authentic leadership and its role in enhancing the productive organizational energy in the Directorate of Passport Affairs in Baghdad, as the research problem indicated that there is a kind of weakness among the leadership of the Directorate, and this is reflected in turn negatively on strengthening the productive organizational energy in it, so the research seeks To introduce the leaders of the community subject of the research to the importance of employing the positive leadership style (Authentic leadership) with its four dimensions (Self-awareness, Ethical perspective, Transparent relations, Balanced treatment) in order to enhance the organizational energy produced in it, Hence the importance of the research in trying to give a set of solutions that would address the problems of the researched organization as far as it relates to the research variables. Adopting the method of direct observation during the visits that the researchers made to the directorate, and the research community included the senior and middle administrative leaders in the directorate, represented by (the general manager, heads of departments, assistant heads of departments, officials of the divisions). And that is based on the intentional sampling method that included the senior and middle leaders in it, as the researchers distributed (82) questionnaires to the community to be studied, and (75) questionnaires were retrieved, of which (4) were not valid for statistical analysis, so that the number of questionnaires became (71), a questionnaire that represented The research community to be studied, and the two researchers relied on completing the practical aspect of the research on the statistical package (SPSS V.23). direct, while the balanced treatment achieved the highest correlation and effect on the level of variable dimensions. Kye Words: Authentic leadership, Productive organizational energy, Directorate of passports affairs Baghdad